Public Health and Environmental Problems: Study on the Bhur Bhur Pochamma Tribe in Latur District of Maharashtra, India - Rahul Sarwade (Three E Science Institute, 2021)
An ex-slave Pochamma are amongst the most marginalized community in the Latur district of Maharashtra. This paper focuses on their health status and practice disease and illness. This research aims to study the significant health problem the Pochamma community faces. The research design used is Qualitative Exploration so that phenomena from everyone's personal experience can be explored with the help of an in-depth interview; the study examines the primary issue from expertise shared by the tribal population to bring out health issues and health care services. The paper's outcome deals with the issues and concerns related to water and skin-related diseases among the Pochamma community. This paper also attempted to explain how these diseases are interrelated to water and migration. The lack of resources made them habitual with the current lifestyle. Therefore, it is essential to understand what kind of practices they use to overcome diseases. The study paints a precise but gray picture of this community, excluded from securing benefits of advances like globalization and liberalization due to the unfortunate fact that their existence in the world still needs to be realized.